Vitamin E Phosphate Nucleoside Prodrugs: A Platform for Intracellular Delivery of Monophosphorylated Nucleosides - Richard Daifuku; Michael Koratich; Murray Stackhouse (MDPI AG, 2018)
Vitamin E phosphate (VEP) nucleoside prodrugs are designed to bypass two mechanisms of tumor resistance to therapeutic nucleosides: nucleoside transport and kinase downregulation. Certain isoforms of vitamin E (VE) have shown activity against solid and hematologic tumors and result in chemosensitization. Because gemcitabine is one of the most common chemotherapeutics for the treatment of cancer, it was used to demonstrate the constructs utility. Four different VE isoforms were conjugated with gemcitabine at the 5' position. Two of these were δ-tocopherol-monophosphate (MP) gemcitabine (NUC050) and δ-tocotrienol-MP gemcitabine (NUC052). NUC050 was shown to be able to deliver gemcitabine-MP intracellularly by a nucleoside transport independent mechanism. Its half-life administered IV in mice was 3.9 h. In a mouse xenograft model of non-small cell lung cancer (NSCLC) NCI-H460, NUC050 at a dose of 40 mg/kg IV qwk × 4 resulted in significant inhibition to tumor growth on days 11-31 (p < 0.05) compared to saline control (SC). Median survival was 33 days (NUC050) vs. 25.5 days (SC) ((hazard ratio) HR = 0.24, p = 0.017). Further, NUC050 significantly inhibited tumor growth compared to historic data with gemcitabine at 135 mg/kg IV q5d × 3 on days 14-41 (p < 0.05). NUC052 was administered at a dose of 40 mg/kg IV qwk × 2 followed by 50 mg/kg qwk × 2. NUC052 resulted in inhibition to tumor growth on days 14-27 (p < 0.05) and median survival was 34 days (HR = 0.27, p = 0.033). NUC050 and NUC052 have been shown to be safe and effective in a mouse xenograft of NSCLC.